The Impact of Taxation on the Equalizing Effect of Social Insurance to Income Inequality: a Comparative Analysis of Ten Welfare States - Tommy Ferrarini; Kenneth Nelson (Luxembourg Income Study (LIS), 2002)
Welfare state regimes vary in their redistribution strategies. Some welfare states have extensive taxable social insurance schemes, while others rely more on non-taxable means-tested benefits. In order to assess the distributive effects of different program types, it is necessary to analyze social insurance after taxes, something rarely practiced in comparative research. In this paper, we evaluate distributive effects of social insurance after taking taxes into account in ten welfare states. However, a study of net social insurance raises estimation problems in countries where spouses are taxed separately and income data only is reported on household level. The paper therefore includes a series of validity tests of estimated levels of social insurance after taxes. The main conclusion is that it is possible and necessary to estimate social transfers net of taxes in order to not misspecify the redistributive outcome of social insurance in both inter-country and intra-country analyses of income distributions. The analyses are based on micro level income data from the Swedish Level of Living Survey (LLS) and the Luxembourg Income Study (LIS) including ten countries.
Keywords: 330; Einkommensumverteilung; Sozialstaat; Sozialversicherung; Steuerbelastung; OECD-Staaten